Genetic variation among Asian populations of rice planthoppers, Nilaparvata lugens and Sogatella furcifera (Hemiptera: Delphacidae): mitochondrial DNA sequences - Mun, J.H.; Song, Y.H.; Heong, K.L.; Roderick, G.K. (Cambridge University Press, 1999)
Many species of insects associated with cultivated rice do not over-winter in Korea and Japan, but migrate into these areas each year. To understand better the origins of these immigrations as well as the geographic structure of rice pests in Asian rice growing regions, intraspecific variation in two species of delphacid planthoppers,Nilaparvata lugens(Stål) andSogatella furciferaHorvath, was examined. An 850 base pair region of mitochondrial DNAcytochrome oxidase-I (CO-I) was sequenced from a total of 71 individuals collected from 11 localities in seven countries: Korea, Philippines, China, Bangladesh, Malaysia, Vietnam and Thailand. InN. lugens, three haplotypes were found and all populations sampled shared a dominant haplotype. Localities in Korea contained two haplotypes and localities in China and the Philippines contained three. However, in samples from the Indochina peninsula no variation was detected either within or between populations, consistent with a hypothesis of regular migration and gene flow. These populations did not contain some haplotypes found in Korea, suggesting they were not the source of yearly immigration into Korea and, by extension, Japan. Populations from China did share haplotypes with Korea, which was consistent with the hypothesis that China was the source for yearly immigration into Korea. There was insufficient resolution to distinguish among populations in China. ForN. lugens, the data suggested that populations south of the Red River Valley in Vietnam experienced regular mixing and were distinct from populations to the north which contributed to yearly immigrations. InS. furcifera, there was less differentiation among populations. Two haplotypes were found in all populations except Malaysia. The results for both species were consistent with seasonal weather data and indicated that more detailed analysis of DNA sequence data will be fruitful.